The effect of deviations from precise [001] tensile direction on creep of Ni-base single crystal superalloys. (15th January 2022) - Heep, L.; Bürger, D.; Bonnekoh, C.; Wollgramm, P.; Dlouhy, A.; Eggeler, G.
Abstract: Low temperature (1023 K) high stress (800 MPa) tensile creep behavior of the superalloy single crystal ERBO-1 (CMSX-4 type) is investigated. Three loading directions are compared: precise [001] and 15 ° deviations from [001] towards [111] and [011]. It is found that creep rates ε ˙ scale as ε ˙ [ 001 ] → [ 111 ] > ε ˙ [ 001 ] > ε ˙ [ 001 ] → [ 011 ] already in the early stages of creep ( ε ≤ 1 % ), where dislocation network formation and planar fault intersections cannot rationalize the observed rate effects. An analysis based on Peach-Köhler force calculations suggests, that fast creep rates are observed, when dislocations from two octahedral systems, which are required to react and form the leading part of a planar fault ribbon in the γ'-phase, experience similar driving forces. Creep data, micromechanical calculations and TEM results are in good qualitative agreement. From a technological point of view, the results show that while 15 ° deviations from [001] towards [011] can be tolerated, deviations towards [111] must be avoided. Graphical abstract: Image, graphical abstract